A Comparative Study of Fashion Illustration Project Assessment among Teachers and Students - Amos, Emmanuel; Fobiri, George Kwame; Crentsil, Timothy; Oppong, Diana; Timpabi, Ama Kour (Papanda Publisher, 2024)
This paper explores the assessment of student projects in fashion design by comparing the evaluations of teachers and students (peers). Peer assessment (PA) is increasingly recognized as a valuable tool for enhancing students' assessment skills and providing alternative perspectives on project quality. However, concerns persist regarding the reliability and validity of peer assessments compared to those of teachers. To address this gap, this study aims to compare the assessments of teachers and students, focusing on variables such as Self, FIT, COLOUR, DRAWN, and BEAUTY in fashion design projects. The study used simple random sampling to sample 10 designs of Higher National Diploma (HND) two students enrolled in the fashion department of the Creative Arts Faculty. Teh descriptitve and correlation analysis methods were used to analyse the sample gathered. The Descriptives analysis revealed differences in the mean scores and variability between the Student and Teaching Staff groups for the variables Self, COLOUR, FIT, DRAWP, and BEAUTY. Again, a correlation analysis revealed strong positive correlations between various self-perception categories. This results practically implies that peer assessment is a requisite assessment mehtod in higher education, especially for practical courses such as fashion design. Collaborative assessment, especially among peers is therefore recommended to help students build confidence and ensure a sense of ownership of their projects coupled with sharpening their practical skills.